Basic, Structured, or Strategic? A Diagnostic Typology of Generation Z's Untrained AI Prompting Skills - Praherdhiono, Henry; Soepriyanto, Yerry; Kurniawan, Citra; Slamet, Taufik Ikhsan; Rosyidah, Fauziah Nur Aisyah; Hajjah, Rahma Izzatul (Education and Development Research, 2026)
This study investigates the intuitive (